2022
DOI: 10.1136/jitc-2021-003069
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cell activation and senescence induced by intrahepatic microbiota disturbances drive progression of liver cirrhosis toward hepatocellular carcinoma

Abstract: BackgroundThe significance of the relationship between the microbiota and diseases is increasingly being recognized. However, the characterization of tumor microbiome and their precise molecular mechanisms through which microbiota promotes hepatocellular carcinoma (HCC) development are still unclear.MethodsThe intrahepatic microbiota was investigated from tumor, normal adjacent tissues in 46 patients with HCC and normal hepatic tissues in 33 patients with hemangioma by 16S rRNA gene sequencing. Taxonomic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Stenotrophonomoas has the highest relative abundance in UM microbiome, which is consistent with recent report [15]. Previous studies have shown that as a new opportunistic pathogen, patients with longterm neutropenia and exposure to broad-spectrum antibiotics have a higher risk of Stenotrophonomoas infected, leading to pneumonia, bacteremia, catheter-related infection and other diseases [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Stenotrophonomoas has the highest relative abundance in UM microbiome, which is consistent with recent report [15]. Previous studies have shown that as a new opportunistic pathogen, patients with longterm neutropenia and exposure to broad-spectrum antibiotics have a higher risk of Stenotrophonomoas infected, leading to pneumonia, bacteremia, catheter-related infection and other diseases [19].…”
Section: Discussionsupporting
confidence: 89%
“…With the improvement of microbial detection technology, scientists have paid more and more attention to the research of ora. In recent years, variates studies have found that the existence of bacteria in tumor and it is related to the occurrence and development of disease [9,15]. In this study, we found the existence of bacteria in UM for the rst time, explained the characteristics of UM microbiota and its relationship with PRT and clinical features.…”
Section: Discussionsupporting
confidence: 54%
“…Most recently, a higher abundance of S . maltophilia was found in hepatocellular carcinoma microbiota of the patients with cirrhosis, which induced the senescence of hepatic stellate cells and promoted the process of hepatocarcinogenesis ( Liu et al, 2022 ). Notably, we demonstrated for the first time that the upregulation of HDAC5 caused by S .…”
Section: Discussionmentioning
confidence: 99%
“…Before visualization, DAPI was added to the slides. The S. maltophilia probe used for FISH was: GTC GTC CAG TAT CCA CTG C, 5′ modification: Cy3(Liu et al, 2022). Then the images were captured using Confocal Laser Scanning microscopy (Carl Zeiss Microscopy, United States).…”
mentioning
confidence: 99%
“…Cai et al reported that a conserved intracellular bacterial profile was detected in breast cancer, which played an important role in promoting cancer metastasis (22). Studies of hepatocellular carcinoma (HCC) have found that patients with HCC exhibited imbalances in the tumor microbiome, with a higher abundance of S. maltophilia, which induced the expression of senescence-associated secretory phenotype in hepatic stellate cells and liver cirrhosis, contributing to the progression of HCC (23). Specific gut bacteria can invade CRC tumor tissue (24); therefore, the gut microbiome does not fully reflect the microbial composition in tumors, owing to differences in the invasive and colonizing abilities of different bacteria.…”
Section: Discussionmentioning
confidence: 99%